Penegakan Hukum Terhadap Pelaku Tindak Pidana Korupsi (Tinjauan Hukum Pidana Dan Dalam Perspektif Pidana Islam) - Syarif Fadillah (Jurnal Program Pascasarjana Ilmu Hukum Universitas Islam As-Syafi'iyah, 2023)
Indonesia is the fifth most corrupted country in Southeast Asia, this can be seen in the International Transparency (IT) record, which shows its GPA number at 38 in 2021, up one number from 37 previously. Although it is still below Vietnam, but the status as the fifth most corrupted country, quite painful. The punishment applied to perpetrators of Corruption Crimes is still imprisonment and a fine, not the capital punishment. Law No. 20 of 2001, Amendments to Law no. 31 of 1999, concerning the Eradication of Corruption Crimes, in Article 2 Paragraph (2), indeed limits the imposition of the death penalty only on Corruption Crimes in certain circumstances, for example Corruption Crimes during and/or during National Natural Disasters. Imprisonment and fines that have been carried out against perpetrators of Corruption Crimes, do not deter perpetrators and do not make the public afraid of committing Corruption Crimes, Again, Arrest hand operation (OTT) by the Corruption Eradication Commission, or the Attorney General's Office, we often see and hear of perpetrators of criminal acts of corruption, then should the death penalty be applied to perpetrators of criminal acts of corruption, and what is the Islamic perspective on corruption. In the view of Islamic criminals, corruption crimes include Jarimah Khirobah which in Surah Al-Maidah verse 33, the punishment is death or crucifixion.